1999
DOI: 10.3109/02841859909175600
|View full text |Cite
|
Sign up to set email alerts
|

Spio-MR Imaging versus Double-Phase Spiral CT in Detecting Malignant Lesions of the Liver

Abstract: SPIO-MR produced a significantly better detection rate for malignant focal liver lesions compared with double-phase spiral DPS-CECT but was associated with a higher rate of false-positive findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 35 publications
(39 reference statements)
0
13
0
Order By: Relevance
“…Three radiologists independently reviewed all CT and MR images using the following imaging criteria: HCCs were defined as hypoattenuating lesions at CTAP and as hyperattenuating lesions at CTHA, showing peak of contrast enhancement in the arterial phase, and a rapid washout of contrast in the portal phase on the Gd-DTPA enhanced dynamic MR images, and showing high intensity due to little or no particle uptake on SPIO-enhanced MR images [1,3,9,13]. A dysplastic nodule was defined as a nodule with high intensity on unenhanced T1-weighted MR images and low-or isointensity on unenhanced T2-weighted MR images, showing no contrast enhancement on Gd-DTPA-enhanced dynamic MR images, and showing low intensity on SPIO-enhanced MR images [14].…”
Section: Imaging Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Three radiologists independently reviewed all CT and MR images using the following imaging criteria: HCCs were defined as hypoattenuating lesions at CTAP and as hyperattenuating lesions at CTHA, showing peak of contrast enhancement in the arterial phase, and a rapid washout of contrast in the portal phase on the Gd-DTPA enhanced dynamic MR images, and showing high intensity due to little or no particle uptake on SPIO-enhanced MR images [1,3,9,13]. A dysplastic nodule was defined as a nodule with high intensity on unenhanced T1-weighted MR images and low-or isointensity on unenhanced T2-weighted MR images, showing no contrast enhancement on Gd-DTPA-enhanced dynamic MR images, and showing low intensity on SPIO-enhanced MR images [14].…”
Section: Imaging Analysismentioning
confidence: 99%
“…Furthermore, the combination of CTAP and CTHA has been investigated as a means of improving the accuracy of detection of HCC [4,5]; however, because of the high number of false-positive findings and its invasive nature, CTAP has not achieved widespread use. With the advent of faster, more effective MR protocols, the diagnostic use of multiphasic dynamic MR images [6,7,8], and superparamagnetic iron oxide (SPIO)-enhanced MR images [9,10,11], which is also less invasive than CT angiography, has achieved wider acceptance. We hypothesize that the combination of Gd-DTPA-enhanced dynamic and SPIO-enhanced MR images improves the accuracy of detecting HCC as compared with the more invasive diagnostic approach using combined CTAP and CTHA; therefore, we compared Gd-DTPA-enhanced dynamic MR images, SPIO-enhanced MR images, combined Gd-DTPA-enhanced dynamic and SPIO-enhanced MR images, and combined CTAP and CTHA, in the detection of HCC using receiver operating characteristic (ROC) analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Ferumoxidesenhanced MR imaging may be most useful clinically in the detection of liver metastases and hepatocellular carcinomas [2][3][4][5][6][7][8][9][10][11]. Previous studies showed that ferumoxides-enhanced MR imaging is more accurate than dual-phase helical CT for detecting focal liver lesions [28][29][30], and our unpublished data show that the mean sensitivity of ferumoxides-enhanced MR imaging (94%) for the preoperative detection of hepatocellular carcinoma is significantly greater than that of triple-phase helical CT (84%). Studies have shown that ferumoxides-enhanced MR imaging has a performance comparable to that of CT during arterial portography for the detection of liver metastases [31,32] and hepatocellular carcinomas [6], which suggests that ferumoxides-enhanced MR imaging may have a role as a replacement for CT during arterial portography for the preoperative examination.…”
Section: A B C Dmentioning
confidence: 99%
“…Magnetic Resonance Tomography (MRI) is a sensitive tool for the detection of edema during follow up after irradiation. Adding the RES directed contrast agent Standard Superparamagnetic Iron Oxide (SSPIO, Resovist 1 , Bayer Schering, Berlin, Germany) or the hepatocyte directed contrast agent Gadobenate dimeglumine (Gd-BOPTA, Multihance 1 , Bracco, Princeton, NJ, USA) to the MRI examination enables the visualization of eventual function loss of the hepatic RES and hepatocytes with a high contrast to noise ratio (Stark et al 1988, Kopp et al 1997, Muller et al 1999, Rohlfing et al 2000, Schnorr et al 2006. The clinical end-point is SSPIO and Gd-BOPTA-enhanced MRI visualization of the loss of phagocytosis of the RES and the loss of hepatocyte function, respectively.…”
Section: Introductionmentioning
confidence: 99%